2011
DOI: 10.1128/ec.00296-10
|View full text |Cite
|
Sign up to set email alerts
|

Role of B Regulatory Subunits of Protein Phosphatase Type 2A in Myosin II Assembly Control in Dictyostelium discoideum

Abstract: In Dictyostelium discoideum, myosin II resides predominantly in a soluble pool as the result of phosphorylation of the myosin heavy chain (MHC), and dephosphorylation of the MHC is required for myosin II filament assembly, recruitment to the cytoskeleton, and force production. Protein phosphatase type 2A (PP2A) was identified in earlier studies in Dictyostelium as a key biochemical activity that can drive MHC dephosphorylation. We report here gene targeting and cell biological studies addressing the roles of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Myosin IIa has been identified as a tumor suppressor in squamous cell carcinoma (63). There is evidence that PP2A-dependent dephosphorylation of myosin IIa exerts some influence over filament assembly (75). However, the molecular details of how PP2A regulates myosin IIa function to drive tumor suppression are unknown and warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Myosin IIa has been identified as a tumor suppressor in squamous cell carcinoma (63). There is evidence that PP2A-dependent dephosphorylation of myosin IIa exerts some influence over filament assembly (75). However, the molecular details of how PP2A regulates myosin IIa function to drive tumor suppression are unknown and warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The defects in the 3XASP and 3XALA mutants indicate that the phosphorylationdephosphorylation cycle plays a role both in basic cell motility and chemotaxis. This cycle is regulated by myosin heavy chain kinases and phosphatases (Murphy and Egelhoff, 1999;Rai and Egelhoff, 2011), which one would assume are the targets of signal transduction pathways that coordinate remodeling of the cortical cytoskeleton during basic cell motility and chemotaxis.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies suggested that PP2A plays a role in cytoskeleton regulation [ 22 25 ], they did not provide a detailed picture of the underlying mechanism. Here, by using Drosophila as a model organism, we investigated the biological function of a specific regulatory subunit in actin polymerization.…”
Section: Resultsmentioning
confidence: 99%